2016
DOI: 10.1515/bj-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Regarding Organ Donation among Medical Students

Abstract: Introduction. All over the world people on organ transplant waiting lists die due to shortage of donor organs. The success of organ donation program needs education of the population regarding organ donation for which healthcare professionals are most suitable. The present study was taken up to assess the knowledge and attitude of 1st, 2ndand 3rdyear medical students about organ donation. Methods. A specially designed self-administered questionnaire was distributed amongst all willing 1st, 2nd and 3rdyear medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…The results are similar to those reported by Bharambe VK et al, where 87% of the respondents were aware of need for legal supervision. 13 As far as awareness about legal age for organ donation is concerned, more than three fourth (77.50%) of the respondents had correct knowledge. In a study by Kaur S et al, only half of the respondents were aware about legal age of the organ donation in India.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The results are similar to those reported by Bharambe VK et al, where 87% of the respondents were aware of need for legal supervision. 13 As far as awareness about legal age for organ donation is concerned, more than three fourth (77.50%) of the respondents had correct knowledge. In a study by Kaur S et al, only half of the respondents were aware about legal age of the organ donation in India.…”
Section: Discussionmentioning
confidence: 96%
“…However, Bharambe VK et al, reported a lower awareness about existing laws to the tune of 57.6%. 13 Every nation has its own laws to regulate organ donation and transplantation. In this context the results are not in agreement with those reported by Hamed H et al, from Egypt where 83% of the respondents thought there was no law regulating organ donation or didn't hear or read about the law.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were studies which reported adequacy of knowledge among health-care professionals such as doctors, nurses, undergraduate, and postgraduate medical students. [ 11 12 13 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%